A study on the students’ ability in using english prepositions (on, in, at, before, under): a survey at the first semester students of english language education - Terasne (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
This study aims to determine students’ ability in using English prepositions and to identify the problems they face. The research method used was a descriptive qualitative method. The data were collected through a grammar test. The sample consisted of 37 first-semester students of the English Language Education Study Program in the academic year 2025/2026. The data were analyzed by classifying students’ scores, where scores of 66–100 were categorized as able and scores of 0–65 as unable. The results showed that 20 students (52%) were categorized as able, while 17 students (47%) were categorized as unable. In addition, most errors were found in the use of prepositions such as in, on, and at due to their similar meanings and multiple functions. Therefore, it can be concluded that students’ ability in using English prepositions still needs improvement.